Srovnání prezentace kasin v České republice a u amerických indiánů - Pěničková, Daniela (Lidé města, 2002)
This article explores and compares the performance and public face of gambling industry, in particular casino resorts, in the Czech Republic (Prague) and American lndian Country (American Indian tribe from Oregon, and Arizona). ln the main body of the article, l explore both Czech and Native American casino settings within six major areas: physical environment, social geography, time, guests and stuff, gender and age, and ethnicity. Analyzing each area, I illuminate what management strategies are used and how they work in attracting the public in both countries . Drawing upon exploration of these six areas, the article discusses the question of what makes the casinos marketable and how the traditional culture of Bohemian and Native American peoples is presented - brokered, using the term of Richard Kurin - in the public performance of these casinos. ln conclusion, I discuss the performative element of Czech and Native American casinos in the context of Barbara Kirshenblatt-Gimbletťs destination culture, which is a concept developíng the notion that in order for the tourist industry to thrive, cultural institutions are structured and conceptualized as venues of tourist destination.